Exposure of children to fine particles (PM2.5 and PM10) in schools in the health districts of Yopougon, Abidjan - Attoh-Toure, Harvey; Oussou, Konan Roland; Coulibaly, M'Begnan; Soualihou, Noufé; Konan, N'Guessan; Gilbert, Loukou Konan; Kouao, René; Koné, Mohamed; Tiembré, Issaka; Dagnan , Simplice N'Cho (International Journal Of Community Medicine And Public Health, 2024)
Background: In Africa, the school environment is becoming a growing concern, as concentrations of fine particles inside classrooms are very high. We decided to estimate the level of exposure to PM2.5 and PM10 of schoolchildren in the health districts of Yopougon in Abidjan. Methods: This was an analytical cross-sectional study of pupils aged 8 to 14 years in the health districts of Yopougon. Our study was conducted from 24 November 2020 to 18 January 2021. The pupils were selected by two-stage random sampling. A real-time fine-particle measurement instrument, the DYLOS 1700, and the ISAAC questionnaire were used to collect the parameters studied. Results: We surveyed 881 pupils from 08 schools. The sex ratio (M/F) of the pupils was 0.9 and the mean age was 12 years. Measurements of PM2.5 and PM10 levels in the classrooms were 30 times higher than WHO standards and ranged from 200 to 1000 µg/m3 and 1000 to 3000 µg/m3 respectively. There was a significant link between the presence of pollution sites near schools and the increase in PM2.5 and PM10 levels in classrooms. Clinical manifestations suggestive of asthma in pupils were significantly associated with high levels of PM2.5 and PM10. Conclusions: Pupils in Yopougon’s schools are exposed to high level of fine particle pollution that exceed WHO standards. Respecting and applying pollution reduction measures will help to create a school environment that is favourable to the respiratory health of pupils.